Development of EYK - Helgi Gylfason 1986- (2015)
EYK is a data processing system that has been in development for two years and is on the verge of being sold to its first customer. Originally it was only supposed to replace an in-house system at Reykjavik Energy however the idea arose that EYK could be useful for other energy companies in Iceland. Therefore, in the first year of development, much work was put into researching the Icelandic energy market. In this research, the operations of the energy companies were examined and use cases were found. By the end of the first year it was apparent that enough companies would benefit from using EYK to warrant founding a private company around it. The small size of the team created a challenge for developing and delivering EYK. Both team members have a greater responsibility than they would have in a larger team and they do not have the privilege to specialize themselves in one thing. In order to make it possible for them to develop EYK at a sufficient pace, to service its users and run a private company the work environment had to be made efficient. The team work was organized using agile (Scrum) methods and the work on the source code was orchestrated with a customized Git branching model. As a small team cannot afford spending much time on fixing errors, testing was integrated into the development cycle with a test-first approach. Finally as EYK will be set up at customer’s servers it is simply not sustainable for two people to maintain them manually. Therefore a configuration management system is used to automate most of the processes e.g. the deployment of EYK to customers servers.